OPTIMASI PARAMETER PROSES 3D PRINTING TERHADAP KEKUATAN TARIK FILAMENT POLYETHYLENE TEREPHTHALET GLYCOL - Rovi Avriansah; Pristiansyah Pristiansyah; Erwanto Erwanto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
3D printing technology is the latest technology in the field of Additive layer manufacturing (AM). One of the AM that is currently being developed is Rapid Prototyping (RP) based on FDM, the FDM type uses polymer melted by heating then extruded through a nozzle as ink and deposited on the printer table to produce 3D objects layer by layer (layer by layer). In this research, the filament used is PETG (Polyethylene terephthalate Glycol) filament. In this study, the taguchi L9 () OA method was used. This study aims to determine the effect of the process parameters used in tensile testing in accordance with the process parameters used, namely Nozzel Temperature, Bed Temperature, Wall Thicknes, and Infill Speed. The results showed that the parameters that greatly influenced the tensile test using PETG filament were Bed Temperature (70°C), Nozzle Temperature (230°C), Wall Thickness (0.8 mm), and Infill Speed ​​(40 mm/s).